2001
DOI: 10.1038/sj.ejhg.5200752
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide linkage analysis of Scandinavian affected sib-pairs supports presence of susceptibility loci for celiac disease on chromosomes 5 and 11

Abstract: Celiac disease (CD) is a common chronic inflammatory disorder of the small intestine with a multifactorial aetiology. HLA is a well-known risk factor, but other genetic factors also influence disease susceptibility. To identify the genes involved in this disorder, we performed a genome-wide scan on 106 well-defined Swedish and Norwegian families with at least two affected siblings. We investigated familial segregation of 398 microsatellite markers, and utilised non-parametric linkage analysis. The strongest li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 31 publications
0
69
1
Order By: Relevance
“…5 Apart from the HLA region, only 5q31-33, with a maximum Zlr ¼ 4.39 (P ¼ 6 Â 10 À6 ), showed genome-wide significant linkage according to standard thresholds. 6 Linkage of CD to this region was originally identified by Greco et al 7 and was also found by Naluai et al 8 and Liu et al 9 Evidence for a risk factor in 2q33 (CELIAC3), likely corresponding to the CTLA4/ICOS genes, comes from association studies mainly in Northern Europe populations. 10 The CELIAC4 locus was mapped to 19p13.1 with a maximum logarithm of odds score ¼ 4.43 in a cohort of 101 affected sib pairs belonging to 82 Dutch families.…”
Section: Introductionmentioning
confidence: 77%
“…5 Apart from the HLA region, only 5q31-33, with a maximum Zlr ¼ 4.39 (P ¼ 6 Â 10 À6 ), showed genome-wide significant linkage according to standard thresholds. 6 Linkage of CD to this region was originally identified by Greco et al 7 and was also found by Naluai et al 8 and Liu et al 9 Evidence for a risk factor in 2q33 (CELIAC3), likely corresponding to the CTLA4/ICOS genes, comes from association studies mainly in Northern Europe populations. 10 The CELIAC4 locus was mapped to 19p13.1 with a maximum logarithm of odds score ¼ 4.43 in a cohort of 101 affected sib pairs belonging to 82 Dutch families.…”
Section: Introductionmentioning
confidence: 77%
“…Still, some linkage to the region has been reported in a few studies 68,100,74 and most published studies in CD do show signs of association as well. 100,74,101 -111 However, they are not completely congruent.…”
Section: Fine-mapping and Positional Candidates On Chromosomes 5 And 19mentioning
confidence: 99%
“…64 These were the second, third, fourth and fifth studies published. 62,66,68,69 The raw data consisted of genotypes from 442 families; 2025 individuals of whom 1056 are affected. The results pointed to chromosome 5q31 -33 as being the only significant locus in these families apart from HLA ( Figure 2 Figure 1 The HLA-DQ2 ab heterodimer encoded in cis and in trans.…”
Section: Epidemiology Population Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Box 6511, Aurora, Colorado 80045, The fact that HLA-specific relative risk to siblings is 2.3-5.5 [1] compared to the overall relative risk to siblings of 30-60 suggests that non-HLA genes play a large role in the etiology of CD. Several linkage studies, either of candidate genes or whole genome screens, to find non-HLA genes have been performed (e.g., [2,[8][9][10][11][12][13][14][15][16][17][18]), but few regions have been replicated, and replication has occurred only in studies of European or European-derived populations. The exceptions are the HLA region, which consistently shows extremely strong evidence of linkage to CD, and three regions, 2q33, 11p11 and 5q31-33.…”
Section: Introductionmentioning
confidence: 99%